Method for synthesizing alpha-olefin by adopting composite molding catalyst
By adding rare earth elements to the iron-based catalyst and controlling the CO2 content in the raw gas, the problem of insufficient stability of the α-olefin reaction system for synthesis gas is solved, and the stability and selectivity of the catalyst are improved.
Patent Information
- Application Number
- CN202311278536.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-28
AI Technical Summary
The stability of the α-olefin reaction system for syngas is insufficient, resulting in the catalyst being prone to carbon accumulation and inactivation and low selectivity.
Add an appropriate amount of rare earth elements to the iron-based catalyst, and control the appropriate CO2 content in the raw material gas, regulate the Fe5C2/Fe3O4 ratio of the iron active component in the catalyst, and maintain the stability of the reaction system.
It significantly improves the reaction stability of the catalyst, reduces the generation of heavy hydrocarbons and the amount of carbon deposits, and extends the service life of the catalyst.
Smart Images

Figure CN119701973A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of olefin preparation, and in particular to a method for synthesizing alpha-olefin by using a composite shaped catalyst. Background Art
[0002] As an important process for producing α-olefins from non-petroleum resources, the production of α-olefins from synthesis gas has attracted much attention. The most studied route is the production of α-olefins from synthesis gas through Fischer-Tropsch synthesis, but the distribution of product hydrocarbons is affected by the Amderson-Schulz-Flory (ASF) distribution, the carbon number distribution of olefin products is relatively wide, and the selectivity of both low-carbon olefins and high-carbon olefins is low. How to improve the carbon number distribution of Fischer-Tropsch synthesis hydrocarbon products and improve the distribution of target product olefins is the goal of current research on the production of α-olefins from synthesis gas, and catalyst research and development has always been one of the main ways to improve this goal.
[0003] Among the many catalysts studied, iron-based catalysts, as the most studied and cheapest Fischer-Tropsch catalysts, are naturally ideal candidates for the development of synthesis gas to alpha-olefin catalysts. The conversion rate and selectivity of the iron-based catalysts for synthesis gas to alpha-olefins studied recently have been improved. For example, CN109865515A discloses a preparation method for synthesis gas to alpha-olefin catalysts, CN114369002A discloses a two-stage composite catalyst for synthesis gas to alpha-olefins, and CN114369003A discloses a pretreatment method for synthesizing alpha-olefin catalysts, all of which contribute to the improvement of product selectivity in the synthesis gas to alpha-olefin process. However, for the synthesis gas to alpha-olefin reaction system, the stability of the system is still insufficient, and how to improve the stability of the reaction system is still a challenging problem in this research.
[0004] CN114369002A discloses a method for synthesizing linear α-olefins from syngas, comprising the following steps: synthesizing linear α-olefins with a carbon number of 6-15 through a pretreated composite catalyst under the conditions of 200-380°C and 0.5-5.0MPa; wherein the composite catalyst comprises two-stage catalysts, one-stage catalyst is an iron-based catalyst, and the iron-based catalyst has iron oxide and / or iron-containing carbide as active components; the second-stage catalyst is a nickel-based catalyst or a cobalt-based catalyst, and the nickel-based catalyst has nickel oxide as an active component, and the cobalt-based catalyst has cobalt oxide as an active component. CN109865515A discloses a method for preparing a catalyst for preparing linear α-olefins from syngas, and the technology uses one or more alkali metal elements K, Mg, Ca, etc. as electronic additives for the iron catalyst to prepare an efficient syngas conversion catalyst, enhance the carbon chain growth ability, and improve the selectivity of linear α-olefin products. However, the stability of the syngas-to-α-olefin reaction system studied in these two technologies needs to be further improved.
[0005] CN114369003A discloses a pretreatment method for a catalyst for synthesizing α-olefins, which comprises the following steps: sequentially performing the three steps of reduction, carbonylation, and re-reduction, wherein the reduction and re-reduction conditions are the same or different, wherein the reduction and re-reduction refer to the conditions of a reducing atmosphere containing hydrogen, at 250-500°C, 0.01-5.0MPa, and a reducing atmosphere space velocity of 1000-50000ml·h -1 ·gCat -1 The catalyst is reduced under the conditions of 2-30 hours; the carbonylation refers to the carbonylation under the atmosphere containing CO at 250-450°C, 0.01-5.0MPa, and a gas space velocity of 500-50000ml·h -1 ·gCat -1 The carbonylation catalyst is used for 3-50 hours under the conditions of 100 ℃ and 200 ℃. Although the purpose of this technology is to solve the problems of low α-olefin selectivity and poor catalyst stability in the traditional synthesis gas conversion process, the stability of the reaction system studied by this technology still needs to be further improved. Summary of the invention
[0006] To solve the above problems, the object of the present invention is to provide a method for synthesizing α-olefins, which can ensure the stability of the reaction system for synthesizing α-olefins.
[0007] To achieve the above object, the present invention provides a method for synthesizing α-olefins, which comprises the following steps:
[0008] The iron-based catalyst modified by rare earth elements is subjected to reduction pretreatment by using hydrogen; wherein the rare earth elements include one or a combination of two or more of La, Ce, and Pr, and the content of the rare earth elements is 0.5-3.0 mol% based on the total molar amount of the metal elements in the iron-based catalyst;
[0009] A raw gas containing hydrogen, carbon monoxide and carbon dioxide is subjected to a reduction pre-treated catalyst to perform a synthesis reaction to obtain alpha-olefins; wherein the molar content of carbon dioxide in the raw gas is 2.0-8.0 mol%, the molar content of hydrogen is 49-86 mol%, and the molar content of carbon monoxide is 6-49 mol%.
[0010] According to a specific embodiment of the present invention, preferably, the rare earth element is La.
[0011] In view of the problems of insufficient reaction stability and easy carbon deposition and deactivation of the current iron-based catalyst for synthesizing α-olefins from synthesis gas, the present invention adds an appropriate amount of rare earth metal elements to the iron-based catalyst and controls the appropriate CO2 content in the raw gas to ensure that the iron active components in the iron catalyst are regulated to maintain a suitable Fe5C2 / Fe3O4 ratio during the reaction operation, thereby maintaining the stability of the reaction system.
[0012] The main reason for the deactivation of olefin synthesis catalysts is the carbon accumulation (heavy hydrocarbons) on the catalyst surface. In the synthesis reaction of the present invention, the iron phase of the iron-based catalyst mainly exists in the form of α-Fe, χ-Fe5C2 and Fe3O4. In the initial stage of the synthesis reaction, the α-Fe component formed by high-purity hydrogen reduction activation will react with CO2 and CO in the raw gas to form iron carbide (χ-Fe5C2), and χ-Fe5C2 is the active phase of the synthesis gas and other raw gas to olefin reaction, which can catalyze the Fischer-Tropsch reaction to produce olefins. As the reaction proceeds, the olefins in the reaction atmosphere can in turn promote the formation of iron carbide, inhibit the generation of heavy hydrocarbons, reduce the amount of heavy hydrocarbon carbon accumulation on the catalyst, and prevent the catalyst from deactivating.
[0013] The present invention can maintain the ratio of χ-Fe5C2 / Fe3O4 of active species of the catalyst reaction at a high level by adding rare earth elements such as La, Ce, and Pr to the iron-based catalyst, thereby maintaining the stability of the reaction system. In addition, the addition of rare earth elements can also promote the uniform dispersion of iron elements in the catalyst. At the same time, the present invention also adds CO2 to the raw gas. On the one hand, the combined action of CO2 and high-pressure H2 can promote the generation of active components of iron carbide and inhibit the generation of heavy hydrocarbons; on the other hand, it can effectively reduce the probability of secondary reactions of olefins generated by the reaction. Therefore, the olefin production method provided by the present invention generates less carbon deposits than the prior art within the same reaction time, and the reaction stability of the catalyst is significantly improved.
[0014] According to a specific embodiment of the present invention, preferably, the content of carbon dioxide in the raw gas is 2.0-5.0 mol%.
[0015] According to a specific embodiment of the present invention, preferably, in the raw gas, the molar content of hydrogen is 60-76 mol%, and the molar content of carbon monoxide is 18-32 mol%.
[0016] According to a specific embodiment of the present invention, preferably, in the raw gas, the content of carbon dioxide is 2.0-5.0 mol%, the molar content of hydrogen is 60-76 mol%, and the molar content of carbon monoxide is 18-32 mol%.
[0017] According to a specific embodiment of the present invention, preferably, the volume ratio of hydrogen to carbon monoxide in the raw gas is 2-4.
[0018] According to a specific embodiment of the present invention, preferably, the raw gas is synthesis gas.
[0019] According to a specific embodiment of the present invention, preferably, the temperature of the synthesis reaction is 250-350° C., and the pressure is 1.0-4.0 MPa, preferably 2.0-3.0 MPa.
[0020] According to a specific embodiment of the present invention, preferably, the space velocity of the raw gas is 1000-6000ml·gCat -1 ·h -1 , preferably 2000-5000ml·gCat -1 ·h -1 .
[0021] According to a specific embodiment of the present invention, preferably, the iron-based catalyst modified by rare earth elements contains iron-containing oxides, and the iron-containing oxides include ferrosoferric oxide and / or ferrous oxide.
[0022] According to a specific embodiment of the present invention, preferably, the iron-based catalyst modified by rare earth elements is prepared by a co-precipitation method or an impregnation method.
[0023] According to a specific embodiment of the present invention, preferably, when the co-precipitation method is adopted, the preparation method of the iron-based catalyst modified by the rare earth element is: adding an alkaline solution to a salt solution containing iron elements and rare earth elements to obtain a precipitate, separating the precipitate and drying and calcining it to obtain the iron-based catalyst modified by the rare earth element.
[0024] According to a specific embodiment of the present invention, preferably, when the impregnation method is adopted, the preparation method of the iron-based catalyst modified by the rare earth element is: adding an alkaline solution to a salt solution containing the iron element, separating the precipitate, washing, drying and roasting to obtain the iron-based catalyst, and the iron-based catalyst is impregnated into the salt solution containing the rare earth element. After the impregnation is completed, the solid is taken out and dried and roasted to obtain the iron-based catalyst modified by the rare earth element.
[0025] According to a specific embodiment of the present invention, preferably, the calcination temperature in the coprecipitation method or the impregnation method is 400-500°C.
[0026] According to a specific embodiment of the present invention, preferably, in the pretreatment of the iron-based catalyst modified by rare earth elements, the reduction reaction temperature is 320-380°C and the reaction time is 4-16h. More preferably, the reduction reaction temperature is 350°C and the reaction time is 8h.
[0027] According to a specific embodiment of the present invention, preferably, the iron-based catalyst modified by rare earth elements catalyzes the synthesis reaction in the form of a composite shaped catalyst, and the components of the composite shaped catalyst include the iron-based catalyst modified by rare earth elements, alumina, and graphite, wherein the mass ratio of the iron-based catalyst modified by rare earth elements to alumina is 1-5:1, the ratio of graphite to alumina is 1:4-10, and the mass percentage of alumina in the composite shaped catalyst is 20-50%.
[0028] The reaction of producing α-olefins from synthesis gas by Fischer-Tropsch synthesis is a highly exothermic reaction, which has high requirements on the molding process of iron-based metal oxide catalysts. Since iron-based catalysts have poor self-adhesiveness, they are not easy to mold, and are easy to pulverize after the reaction and have poor strength after molding. Therefore, in order to solve this problem, the present invention further preferably catalyzes the reaction in the form of a composite molded catalyst using the iron-based catalyst modified by the rare earth element.
[0029] The composite formed catalyst of the present invention adds appropriate amounts of alumina and graphite as forming aids, controls the distance of active components and the forming particle size during the forming process, avoids local overheating of the catalyst, and is conducive to timely removal of reaction heat, thereby ensuring the reaction performance of the catalyst. At the same time, the forming aids alumina and graphite form a strong interaction with the catalyst components, thereby improving the strength of the composite formed catalyst and preventing it from being broken and pulverized.
[0030] In some specific embodiments of the present invention, the lateral pressure strength of the composite molded catalyst is increased from 35 N / cm to 90 N / cm. A more obvious effect is that the lateral pressure strength of the catalyst increases from powdered to 63 N / cm after 100 hours of reaction.
[0031] According to a specific embodiment of the present invention, preferably, the components of the composite shaped catalyst also include water, and the mass ratio of water to graphite is 1:10-50, more preferably 1:20-50.
[0032] According to a specific embodiment of the present invention, preferably, in the composite shaped catalyst, the purity of the graphite is ≥99.9%.
[0033] According to a specific embodiment of the present invention, preferably, in the composite shaped catalyst, the iron-based catalyst modified by rare earth elements and alumina are both in granular form, and the particle size of the two is 20-80 mesh, more preferably 40-80 mesh, and further preferably 60-80 mesh.
[0034] According to a specific embodiment of the present invention, preferably, the composite shaped catalyst is cylindrical, with a diameter of 3-6 mm, more preferably 3-4 mm, and a height of 3-8 mm, more preferably 3-5 mm.
[0035] According to a specific embodiment of the present invention, preferably, the method for preparing the composite formed catalyst comprises the following steps:
[0036] (1) dry granulating the iron-based catalyst modified by the rare earth element, and then crushing and screening the catalyst to obtain catalyst particles of a certain size;
[0037] (2) The catalyst particles are mixed with alumina particles and graphite, water is added, and then tablets are pressed to obtain the composite catalyst.
[0038] According to a specific embodiment of the present invention, preferably, the particle size of the granules obtained by dry granulation is 2-5 mm.
[0039] In the catalyst forming process of the present invention, the iron-based catalyst modified by rare earth elements is in powder form, and is made into particles of a certain particle size by dry granulation, and then crushed, and the catalyst of the required mesh size is screened out with a sieve for tableting. Among them, the role of dry granulation is to make the catalyst powder into particles with a larger particle size, which are used for subsequent crushing and screening to obtain the catalyst of the target particle size. The formation process of particles of different particle sizes during the granulation process is different, the binding force between the catalyst powders is different, and the intensity and time required for crushing are also different, all of which have a certain impact on the catalyst strength.
[0040] According to a specific embodiment of the present invention, preferably, the molding pressure is 0.5-3.0 MPa, more preferably 1.0-2.5 MPa.
[0041] The technical solution provided by the present invention has the following beneficial effects:
[0042] The present invention adds an appropriate amount of rare earth metal elements to the iron-based catalyst and controls an appropriate CO2 content in the raw gas to ensure that the iron active components in the iron catalyst are regulated to maintain an appropriate Fe5C2 / Fe3O4 ratio during the reaction operation process, reduce the generation of heavy hydrocarbons and their deposition on the catalyst surface, and thus maintain the activity of the catalyst and the stability of the reaction system. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The Mössbauer spectrum of the catalyst after 500 h of reaction in Example 1;
[0044] Figure 2 This is the Mössbauer spectrum of the catalyst after 500 hours of reaction in Comparative Example 2;
[0045] Figure 3 It is a comparison chart of the reaction stability of the reaction systems of Example 8 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0046] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0047] Example 1
[0048] This embodiment provides a method for synthesizing α-olefins, comprising the following steps:
[0049] (1) Preparation of iron-based catalysts improved by rare earth elements
[0050] 63.78g Fe(NO3)3·9H2O, 94.50g Fe(NO3)2·6H2O and 4.55g La(NO3)3·6H2O were mixed with 500mL water to form an iron salt solution, and 15.30mL of 12.1mol / L HCl solution was added; 500ml of 0.5mol / L K2CO3 solution was added at a uniform rate at 60°C with stirring; within about 2h, the acidic pH value of the solution was adjusted to a pH value of about 9; after the addition was completed, the solution was stirred at a constant temperature for 1h and cooled to room temperature; after the reaction was completed, the deposited product was separated by magnetic field adsorption, washed with deionized water to neutrality, dried, calcined at 450°C, pressed into tablets, and crushed to 20-40 mesh, and the obtained catalyst sample was marked as La-Fe-1-Cat.
[0051] (2) Catalytic reaction
[0052] The catalyst La-Fe-1-Cat obtained in step (1) was filled into a reactor, with a catalyst filling amount of 1 g, and subjected to reduction pretreatment at 350° C. for 8 h under pure hydrogen conditions; after the reduction was completed, the temperature of the reactor was adjusted to 300° C. at a rate of 1° C. / min, and the inlet gas was switched to a reaction raw gas, which was a mixture of H2 / CO / CO2 / N2, with the molar percentages of each gas being H2: 60.6 mol%, CO: 30.3 mol%, CO2: 5 mol%, and N2: 4 mol% (the volume ratio of H2 / CO / CO2 was 2 / 1 / 0.165, with N2 as an internal standard), and the back pressure was set to a reaction pressure of 2.0 MPa. The raw gas was heated to 300° C., 2.0 MPa, and 5000 ml·gCat. -1 ·h -1 The synthesis reaction was carried out under the catalytic conditions of . The catalytic reaction results are shown in Table 1.
[0053] Example 2
[0054] This embodiment provides a method for synthesizing α-olefins, which is the same as that of embodiment 1, except that: in step (1), 4.55 g La(NO3)3·6H2O is replaced by 4.56 g Ce(NO3)6·6H2O, and the obtained catalyst sample is labeled as Ce-Fe-2-Cat; the catalytic conditions in step (2) are replaced by: 320°C, 3.0 MPa, 3000 ml·gCat -1 ·h -1 The catalytic reaction results are shown in Table 1.
[0055] Example 3
[0056] This embodiment provides a method for synthesizing α-olefins, which is the same as that of embodiment 1, except that: in step (1), 4.55 g La(NO3)3·6H2O is replaced by 2.25 g La(NO3)6·6H2O, and the obtained catalyst sample is labeled as La-Fe-3-Cat; the catalytic conditions in step (2) are replaced by: 300°C, 2.0 MPa, 2000 ml·gCat -1 ·h -1 The catalytic reaction results are shown in Table 1.
[0057] Example 4
[0058] This embodiment provides a method for synthesizing α-olefins, which is the same as that of embodiment 1, except that: in step (1), 4.55 g La(NO3)3·6H2O is replaced by 6.55 g La(NO3)6·6H2O, and the obtained catalyst sample is labeled as La-Fe-4-Cat; the catalytic conditions in step (2) are replaced by: 300°C, 3.0 MPa, 2000 ml·gCat -1 ·h -1 The catalytic reaction results are shown in Table 1.
[0059] Example 5
[0060] This embodiment provides a method for synthesizing α-olefins, comprising the following steps:
[0061] (1) Preparation of rare earth element-modified iron-based catalysts
[0062] A rare earth element-free iron-based catalyst, labeled as Fe-Cat, is prepared by the same preparation method as step (1) of Example 1, except that La(NO3)3·6H2O is omitted, and the obtained rare earth element-free catalyst sample is labeled as Fe-Cat;
[0063] The La element was loaded by the impregnation method: 1.55 g La(NO3)3·6H2O was dissolved in 50 ml water to form a La(NO3)3 solution. Then 25 mL of the formed La(NO3)3 solution was taken and used to impregnate 15 g of the above-mentioned iron-based catalyst Fe-Cat at room temperature for 24 h. The sample was then taken out and dried at 100°C and calcined at 400°C. The obtained catalyst sample was labeled La-Fe-5-Cat.
[0064] (2) Catalytic reaction
[0065] The same as step (2) of Example 1, except that the catalytic conditions were replaced by: 310°C, 2.0 MPa, 4000 ml·gCat -1 ·h -1 The catalytic reaction results are shown in Table 1.
[0066] The evaluation conditions for the catalyst La-Fe-5-Cat prepared in Example 5 were the same as those in Example 1, except that the temperature in the evaluation conditions was replaced by 305°C. A 200-hour reaction stability test of the catalyst was carried out, and the reaction results are listed in Table 1.
[0067] Example 6
[0068] This embodiment provides a method for synthesizing α-olefins, which is the same as that of embodiment 1, except that the catalytic conditions in step (2) are replaced by: 300°C, 2.0 MPa, 2000 ml·gCat -1 ·h -1 The catalytic reaction results are shown in Table 1.
[0069] Example 7
[0070] This embodiment provides a method for synthesizing α-olefins, which is the same as that of embodiment 1, except that the catalytic conditions in step (2) are: 300°C, 2.0 MPa, 2000 ml·gCat -1 ·h -1 The molar ratio of each gas in the raw gas (mixed gas of H2 / CO / CO2 / N2) is: H2: 62.66 mol%, CO: 31.33 mol%, CO2: 2 mol%, N2: 4 mol% (volume ratio of H2 / CO / CO2 is 2 / 1 / 0.165). The catalytic reaction results are shown in Table 1.
[0071] Table 1 Catalytic reaction results of Examples 1-7
[0072]
[0073] It can be seen from the results in Table 1 that the catalyst prepared in the embodiment of the present invention exhibits excellent α-olefin production reaction performance, and the reaction system can maintain stability.
[0074] Comparative Example 1
[0075] This comparative example provides a method for synthesizing α-olefins, which is the same as Example 1, except that the catalyst used in this comparative example is the catalyst Fe-Cat prepared in Example 5. The catalytic reaction results are shown in Table 2.
[0076] Comparative Example 2
[0077] This comparative example provides a method for synthesizing α-olefins, which is the same as Example 1, except that the catalyst used in this comparative example is the catalyst Fe-Cat (containing no rare earth elements) prepared in Example 5, and the composition of the raw gas is H2: 64 mol%, CO: 32 mol%, N2: 4 mol% (H2 / CO volume ratio is 2 / 1), and does not contain CO2. The catalytic reaction results are shown in Table 2.
[0078] Comparative Example 3
[0079] This comparative example provides a method for synthesizing α-olefins, which is the same as Example 1, except that there is no CO2 in the feed gas in step (2).
[0080] The catalytic reaction results of Comparative Examples 1-3 are shown in Table 2.
[0081] Table 2 Catalytic reaction results of comparative examples 1-3
[0082]
[0083]
[0084] Wherein, α-olefin / olefin (C%) refers to the ratio of α-olefin to the total amount of olefins in terms of carbon number; in Table 2, C 6-15 = is an olefin with a carbon number of 6-15, C 16-18 = It is an olefin having a carbon number of 16-18.
[0085] According to Table 1 and Table 2, by comparing the catalytic results of Example 1 with Comparative Examples 1 and 2, it can be seen that the reaction system catalyzed by the iron-based catalyst modified by rare earth elements has higher stability than the unmodified Fe-Cat catalyst. By comparing the catalytic results of Example 1 with Comparative Examples 2 and 3, it can be seen that the raw gas containing an appropriate amount of CO2 can significantly modify the stability of the catalyst and the reaction system compared with the raw gas without CO2.
[0086] Figure 1 and Figure 2 The Mössbauer spectra of the catalysts after 500 h of reaction in Example 1 and Comparative Example 2 are shown respectively. Table 3 and Table 4 are Figure 1 and Figure 2The corresponding data.
[0087] Table 3 Mössbauer spectroscopy data of the catalyst after 500 h of reaction in Example 1
[0088]
[0089] Table 4 Mössbauer spectroscopy data of the catalyst after 500 h of reaction in Comparative Example 2
[0090]
[0091]
[0092] From the data results, it can be calculated that the ratio of Fe5C2 / Fe3O4 (in terms of iron element) in the catalyst after 500 hours of reaction in Example 1 is 7.43, and the ratio of Fe5C2 / Fe3O4 (in terms of iron element) in the catalyst after 500 hours of reaction in Comparative Example 2 is 3.65. This proves that the reaction system with appropriate CO2 content in the feed gas and the rare earth element improved catalyst can maintain the Fe5C2 / Fe3O4 ratio of the active species of the catalyst reaction, thereby maintaining the stability of the reaction system.
[0093] In general, the reaction system of the synthesis method of the present invention has excellent reaction stability, which is closely related to the presence of an appropriate amount of CO2 in the raw gas and the rare earth element modification of the catalyst system.
[0094] Example 8
[0095] This example provides a method for synthesizing α-olefins and performs a reaction stability test on the method. The method for synthesizing α-olefins in this example is the same as that in Example 1, except that the catalytic reaction temperature is replaced from 300°C to 305°C. The reaction stability test lasts for 200 hours, and the reaction results are shown in Table 5.
[0096] Table 5 Test results of the stability of the La-Fe-1-Cat catalyst in the synthesis of α-olefins in Example 8
[0097] Reaction time (h) 5 50 100 150 200 CO conversion rate (mol%) 92.8 92.7 92.6 92.4 92.6 Hydrocarbon selectivity (mol%) 60.2 60.4 60.1 60.3 60.0 Olefins / Hydrocarbons (C%) 70.0 70.2 70.1 69.9 70.0 α-Olefin / Olefin (C%) 75.3 75.2 75.1 75.2 75.0
[0098] Figure 3 The reaction stability comparison diagram of the reaction system of Example 8 and Comparative Examples 1-3 is shown. Figure 3 The results show that in the method for synthesizing α-olefins of the present invention, the catalyst maintains good activity and the reaction system also has good stability.
[0099] Example 9
[0100] This embodiment provides a method for synthesizing α-olefins, wherein the catalyst used is a composite formed catalyst, and the method comprises the following steps:
[0101] (1) Preparation of Catalyst
[0102] 2371.5g FeCl3·6H2O, 940.5g FeCl2·4H2O and 135.2g La(NO3)3·6H2O were mixed with 7.5L water to form an iron salt solution, and 382.5mL of 12.1mol / L HCl solution was added. At 60°C and under stirring conditions, about 27.5L of 5% NH3·H2O solution was added at a uniform rate; within about 2 hours, the acidic pH value of the solution was adjusted to a pH value of about 9; after the addition was completed, the solution was stirred at a constant temperature for 1 hour and cooled to room temperature; after the reaction was completed, the deposited product was separated by magnetic field adsorption, washed with deionized water to neutrality, dried, and calcined at 450°C for 4 hours to obtain an iron-based catalyst modified by rare earth elements, i.e., the catalyst body;
[0103] (2) Catalyst molding
[0104] The catalyst body obtained in step (1) is dry granulated to obtain catalyst particles of 2 mm, and the obtained catalyst particles are crushed and screened to obtain catalyst particles of 60-80 mesh; the catalyst particles of 60-80 mesh, alumina particles (whose particle size range is the same as that of the catalyst particles), and graphite are mixed, and after mixing, a suitable amount of water is added by mist spraying, wherein the mass ratio of graphite: water: alumina: catalyst body is 50:1:200:200, and the graphite is high-purity graphite with a purity of ≥99.9%; and then tableting is performed at a molding pressure of 2.5 MPa to obtain a cylindrical catalyst with a diameter of 4 mm and a height of 5 mm (Φ4×5 mm), i.e., a composite molded catalyst;
[0105] (3) Catalytic reaction
[0106] The composite catalyst obtained in step (2) is filled in a reactor, with a catalyst filling amount of 30g, and the composite catalyst is pre-treated with a mixture of hydrogen and nitrogen, the volume concentration of hydrogen is gradually increased from 10% to 100%, and the reduction pre-treatment is carried out at 350°C for 12h; after the reduction is completed, the temperature of the reactor is adjusted to 280°C at a rate of 1°C / min, and the intake gas is switched to a reaction raw gas, the raw gas is a mixture of H2, CO, CO2, and N2, and the molar percentage of each gas is H2: 60.6mol%, CO: 30.3mol%, CO2: 5mol%, N2: 4mol% (H2 / CO / CO2 volume ratio is 2 / 1 / 0.165, N2 is used as an internal standard), and the back pressure is set to a reaction pressure of 2.0MPa, and the raw gas is heated to 280-310°C (the catalyst bed has a temperature gradient with height), 2.0MPa, 2000ml·gCat -1 ·h -1The synthesis reaction was carried out under the catalytic conditions of . The catalytic reaction results are shown in Table 2.
[0107] Example 10
[0108] This embodiment provides a method for synthesizing α-olefins, which is the same as that of embodiment 9, except that:
[0109] In step (2), the mass ratio of graphite: water: alumina: catalyst body is 20:1:200:300;
[0110] The size of the composite catalyst after tableting is Φ3×3mm.
[0111] Embodiment 11
[0112] This embodiment provides a method for synthesizing α-olefins, which is the same as that of embodiment 9, except that:
[0113] The catalyst particles obtained by dry granulation in step (2) have a particle size of 5 mm;
[0114] The mass ratio of graphite: water: alumina: catalyst body is 25:1:100:400.
[0115] Example 12
[0116] This embodiment provides a method for synthesizing α-olefins, which is the same as that of embodiment 9, except that:
[0117] In step (2), the catalyst particles of 5 mm are obtained by dry granulation, and the catalyst particles of 40-60 mesh are obtained by crushing and screening;
[0118] The mass ratio of graphite: water: alumina: catalyst body is 50:1:100:400;
[0119] The size of the composite catalyst after tableting is Φ3×3mm.
[0120] Example 13
[0121] This embodiment provides a method for synthesizing α-olefins, which is the same as that of embodiment 9, except that:
[0122] In step (2), the catalyst particles of 4 mm are obtained by dry granulation, and the catalyst particles of 40-60 mesh are obtained by crushing and screening;
[0123] The size of the composite catalyst after tableting is Φ3×3mm.
[0124] Embodiment 14
[0125] This embodiment provides a method for synthesizing α-olefins, which is the same as that of Embodiment 9, except that the tableting pressure in step (2) is 1.0 MPa.
[0126] Comparative Example 4
[0127] This comparative example provides a method for synthesizing α-olefins, which is the same as Example 9, except that:
[0128] In step (2), the catalyst particles with a size of 20-40 mesh are obtained by crushing and screening;
[0129] The mass ratio of graphite: water: alumina: catalyst body is 50:1:100:400;
[0130] The tableting pressure is 1.0 MPa.
[0131] Comparative Example 5
[0132] This comparative example provides a method for synthesizing α-olefins, which is the same as Example 9, except that:
[0133] In step (2), the catalyst particles of 20-40 mesh are obtained by crushing and screening; and then the catalyst particles of 20-40 mesh are directly pressed into tablets without mixing with other raw materials to obtain a shaped catalyst.
[0134] The catalyst after tableting in this comparative example was difficult to demould.
[0135] Comparative Example 6
[0136] This comparative example provides a method for synthesizing α-olefins, which is the same as Example 9, except that:
[0137] In step (2), the catalyst particles with a size of 20-40 mesh are obtained by crushing and screening;
[0138] The mass ratio of graphite: water: alumina: catalyst body is 10:1:100:400;
[0139] The tableting pressure is 1.0 MPa.
[0140] The catalyst was difficult to demould after tableting in the tableting process of this comparative example.
[0141] Comparative Example 7
[0142] This comparative example provides a method for synthesizing α-olefins, which is the same as Example 9, except that:
[0143] In step (2), the catalyst particles of 20-40 mesh are obtained by crushing and screening;
[0144] The catalyst particles of 20-40 mesh were mixed with graphite and water only, without adding alumina, and the mass ratio of graphite: water: catalyst body was 10:1:400.
[0145] The lateral pressure strength of the composite shaped catalysts obtained in step (2) of the above-mentioned Examples 9-14 and Comparative Examples 4-7 and the lateral pressure strength of the composite shaped catalysts after participating in the catalytic reaction in step (3) for 100 hours were tested.
[0146] The results are shown in Table 6.
[0147] Table 6 Side compression strength of composite molded catalyst before and after reaction
[0148] Composite molding catalyst Strength before reaction, N / cm Strength after reaction, N / cm Example 9 90 63 Example 10 82 55 Embodiment 11 83 57 Example 12 69 52 Example 13 86 65 Embodiment 14 73 48 Comparative Example 4 52 36 Comparative Example 5 39 - Comparative Example 6 50 32 Comparative Example 7 35 -
[0149] The results of the catalytic synthesis reactions of Examples 9-14 and Comparative Examples 4-7 are shown in Table 7 and Table 8, respectively.
[0150] Table 7 Catalytic reaction results of Examples 9-14
[0151]
[0152] Table 8 Catalytic reaction results of comparative examples 4-7
[0153]
[0154] It can be seen from Tables 6 to 8 that the present invention improves the strength of the catalyst and maintains good reaction activity stability by preparing the iron-based catalyst (catalyst body) modified by rare earth elements into a composite formed catalyst.
[0155] Compared with comparative examples 4-7, the catalyst strength and catalyst stability of Examples 9-14 are significantly increased, among which Example 9 shows the best strength index. The CO conversion rate of the catalysts of Examples 9, 10, 11, and 13 decreases by less than 1% after 100 hours of reaction, and the decrease in Examples 12 and 14 is also less than 3.5%, indicating that the catalyst prepared by the present invention has good reaction stability.
[0156] Compared with comparative example 4 using 20-40 mesh catalyst particles and 1.0 MPa pressure for molding, the catalysts prepared in examples 9-14 of the present invention using 40-80 mesh catalyst particles and a molding pressure of 2.5 MPa have higher mechanical strength and reaction activity stability.
[0157] Comparative Example 5 uses 20-40 mesh catalyst particles and does not add other molding components. Although the molding pressure is 2.5 MPa, the strength is significantly worse than that of Example 9. The CO conversion rate decreases significantly after 100 hours of reaction. Moreover, it is difficult to remove the catalyst from the mold after molding. The catalyst has been crushed after the activity stability test, indicating that the molding added components have a great influence on the strength, stability and demolding of the catalyst.
[0158] Comparative Example 6 uses 20-40 mesh catalyst particles, 1.0 MPa pressure, and reduces the amount of graphite added for molding. Compared with Example 9, the strength of the catalyst is deteriorated, and the CO conversion rate decreases significantly after 100 hours of reaction.
[0159] Compared with Comparative Example 4, Comparative Example 6 reduces the amount of graphite added, the strength of the catalyst is slightly lower than that of Comparative Example 4, and difficulty occurs during the demolding process after molding, indicating that the addition of graphite can improve the strength of the catalyst, and make the molding process easy to operate and reduce equipment wear. The CO conversion rate of the catalyst prepared in Comparative Example 6 at 5h and 100h of reaction is lower than that of Comparative Example 4 to a certain extent, indicating that the addition of graphite has a certain effect on the activity and stability of the catalyst.
[0160] In Comparative Example 7, no alumina is added, and the strength of the catalyst is similar to that of Comparative Example 5, with a smaller strength and crushed after the reaction, indicating that alumina is an important component for improving the strength of the catalyst. The strength and stability of the catalyst prepared by adding alumina and graphite in the present invention are significantly improved, providing technical support for the further application of synthesis gas to α-olefin catalysts.
[0161] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment, it is not used to limit the present invention. Any technician familiar with this patent can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.
Claims
1. A method for synthesizing α-olefins, comprising the steps of: The iron-based catalyst modified by rare earth elements is subjected to reduction pretreatment using hydrogen; wherein, The rare earth element includes one or a combination of two or more of La, Ce, and Pr, and the content of the rare earth element is 0.5-3.0 mol% based on the total molar amount of the metal elements in the iron-based catalyst; A raw gas containing hydrogen, carbon monoxide and carbon dioxide is subjected to a reduction pre-treated catalyst to perform a synthesis reaction to obtain alpha-olefins; wherein the molar content of carbon dioxide in the raw gas is 2.0-8.0 mol%, the molar content of hydrogen is 49-86 mol%, and the molar content of carbon monoxide is 6-49 mol%.
2. The method for synthesizing α-olefins according to claim 1, wherein: The rare earth element is La.
3. The method for synthesizing α-olefins according to claim 1, wherein: The content of carbon dioxide in the raw gas is 2.0-5.0 mol%.
4. The method for synthesizing α-olefins according to claim 1, wherein: In the raw gas, the molar content of hydrogen is 60-76 mol%, and the molar content of carbon monoxide is 18-32 mol%.
5. The method for synthesizing α-olefins according to claim 1, wherein: The volume ratio of hydrogen to carbon monoxide in the raw gas is 2-4.
6. The method for synthesizing α-olefins according to any one of claims 1 to 5, wherein: The raw gas is synthesis gas.
7. The method for synthesizing α-olefins according to claim 1, wherein: The temperature of the synthesis reaction is 250-350°C, and the pressure is 1.0-4.0 MPa, preferably 2.0-3.0 MPa.
8. The method for synthesizing α-olefins according to claim 1, wherein: The space velocity of the raw gas is 1000-6000ml·gCat -1 ·h -1 , preferably 2000-5000ml·gCat -1 ·h -1 .
9. The method for synthesizing α-olefins according to claim 1, wherein: The iron-based catalyst modified by rare earth elements contains iron-containing oxides, and the iron-containing oxides include ferrosoferric oxide and / or ferrous oxide.
10. The method for synthesizing α-olefins according to claim 1, wherein: The iron-based catalyst modified by rare earth elements is prepared by co-precipitation or impregnation; Preferably, when the co-precipitation method is adopted, the preparation method of the iron-based catalyst modified by the rare earth element is: adding an alkaline solution dropwise to a salt solution containing iron and rare earth elements to obtain a precipitate, separating the precipitate, washing, drying and calcining to obtain the iron-based catalyst modified by the rare earth element; Preferably, when the impregnation method is adopted, the preparation method of the iron-based catalyst modified by rare earth elements is as follows: an alkaline solution is added dropwise to a salt solution containing iron elements, a precipitate is separated, and an iron-based catalyst is obtained by washing, drying and calcining. The iron-based catalyst is impregnated into a salt solution containing rare earth elements, and after the impregnation is completed, the solid is taken out and dried and calcined to obtain the iron-based catalyst modified by rare earth elements.
11. The method for synthesizing α-olefins according to claim 10, wherein: The calcination temperature in the coprecipitation method or the impregnation method is 400-500°C.
12. The method for synthesizing α-olefins according to claim 1, wherein: In the pretreatment of the iron-based catalyst modified by rare earth elements, the reduction reaction temperature is 320-380° C. and the reaction time is 4-16 hours.
13. The method for synthesizing α-olefins according to claim 1, wherein: The iron-based catalyst modified by rare earth elements catalyzes a synthesis reaction in the form of a composite shaped catalyst. The components of the composite shaped catalyst include the iron-based catalyst modified by rare earth elements, alumina, and graphite, wherein the mass ratio of the iron-based catalyst modified by rare earth elements to alumina is 1-5:1, the ratio of graphite to alumina is 1:4-10, and the mass percentage of alumina in the composite shaped catalyst is 20-50%.
14. The method for synthesizing α-olefins according to claim 13, wherein: The components of the composite shaped catalyst also include water, and the mass ratio of water to graphite is 1:10-50, preferably 1:20-50; Preferably, in the composite shaped catalyst, the purity of the graphite is ≥99.9%.
15. The method for synthesizing α-olefins according to claim 13, wherein: The iron-based catalyst modified by rare earth elements and alumina are both in granular form, and the particle size of the two is 20-80 mesh, preferably 40-80 mesh, and more preferably 60-80 mesh.
16. The method for synthesizing α-olefins according to claim 13, wherein: The composite shaped catalyst is cylindrical, with a diameter of 3-6 mm, preferably 3-4 mm, and a height of 3-8 mm, preferably 3-5 mm.
17. The method for synthesizing α-olefins according to any one of claims 13 to 16, wherein: The preparation method of the composite formed catalyst comprises the following steps: (1) dry granulating the iron-based catalyst modified by the rare earth element, and then crushing and screening the catalyst to obtain catalyst particles of a certain size; (2) The catalyst particles are mixed with alumina particles and graphite, water is added, and then tablets are pressed to obtain the composite catalyst.
18. The method for synthesizing α-olefins according to claim 17, wherein: The particle size of the granules obtained by dry granulation is 2-5 mm.
19. The method for synthesizing α-olefins according to claim 17, wherein: The molding pressure is 0.5-3.0 MPa, preferably 1.0-2.5 MPa.
Citation Information
Patent Citations
Iron-based catalyst used for Fischer-Tropsch synthesis, preparation method and application
CN104815659A
Iron-based catalyst for low-carbon olefin production through CO2 hydrogenation, and preparation and applications thereof
CN106031871A
Modified iron-based catalyst for synthesizing alpha-olefin through hydrogenation of carbon dioxide and preparation method of modified iron-based catalyst
CN115845859A
Method for synthesizing alpha-olefin
CN119702030A
Process for preparing hydrocarbons from carbon dioxide and hydrogen, and a catalyst useful in the process
US20150197462A1